The effect of subclinical experimental Cowdria ruminantium infection on the health and reproductive performance of breeding ewes - Martínez, T.A.; Meltzer, M.I.; Perry, Brian D.; Burridge, M.J.; Mahan, S.M. (Elsevier, 1999)
This study documented the effect on the productivity of Dorper-Merino cross ewes when they became infected with Cowdria ruminantium as would occur in an endemically stable state. A flock of 152 breeding ewes was randomly divided into two matched groups. One group was infected on multiple occasions with C. ruminantium; the other group remained uninfected. The ewes were bred and monitored for one breeding/lambing/weaning cycle. Hematological, reproductive, and health parameters were recorded at regular intervals. Statistically significant differences in hematological values between the two groups were infrequent and transient. No significant differences in weights, mortality rates or reproductive parameters were detected between the two groups. Subclinical C. rumiantium infection did not negatively affect health and reproductive performance of breeding ewes; endemic stability would be a suitable alternative method of controlling heartwater.